An observational survey of emergency department rapid sequence intubation. Issue 5 (1st September 2001) - Butler, J M; Clancy, M; Robinson, N; Driscoll, P
Abstract : Objectives —To study the current practice of rapid sequence intubations (RSIs) in four different emergency medicine training programmes in the UK. Methods —Observational study design involving four regional training programmes (Wessex, North West, Yorkshire, Avon). Data were collected in real time using a previously piloted survey tool. Data were collected by specialist registrars in emergency medicine over a continuous 28 day period. Data collected included: indications for RSI; key timings of RSI procedures; details of RSI practitioner; complications and outcome of procedure. Results —Data from 60 RSIs were recorded and collected. The majority of decisions to perform RSIs were made by emergency physicians (74% cases). Over 50% of the RSIs occurred after 4 pm. Emergency physicians performed 26% of RSIs although the majority were performed by anaesthetists. Most of the given indications for RSIs were based on an assessment of airway protection. Hypoxia was an uncommon reason for RSI in this study (5%). In two thirds of cases the time taken from the decision being made to perform an RSI, to the achievement of successful intubation, was greater than 20 minutes. No failed intubations were recorded, although six other complications (all minor problems) were recorded. There was no significant difference in the response times between anaesthetists and emergency physicians. Conclusions —This study shows that emergency physicians are currently performing RSIs in emergency departments in the UK. It also suggests improvements could be made to patient care. In particular, standards of care should be agreed for the provision of RSI in the emergency department, including the personnel involved and the appropriate training of individuals. RSI activity in emergency departments in the UK should be audited nationally using an agreed audit tool.